Construção e avaliação térmica de um sistema concentrador parabólico com seguidor solar - Oliveira Junior, Gilberto Bueno de [UNESP] (2015)
The searching for renewable energy sources has mobilized much of the scientific community, which work is tireless in pointing out feasible solutions to use clean energy. Solar energy is natural choice among others, because its availability and amount. A known way to use this energy is by focusing solar rays through parabolics, which allow rays concentration to a small area. The advantage of this type of project is to produce thermal energy at high temperatures. This energy has a wide application on producing other forms of energy such as electric power in turbines since solar concentrators provide steam at high pressure and temperature. The goal of this study is to build a solar concentration device and measure the energy produced, as well its efficiency in transformation. Thus, was built up a parabolic concentrator and a solar tracker to motion in three dimension, which allows device alignment towards incidence of solar rays. Was utilized a pumping system to flowing thermal fluid at high temperatures through the absorber. The energy balance of this thermal fluid, led to obtain behavior curves of net power and system efficiency. The experimental was divided in two parts. On the first one, was obtained the stagnation temperature and the other one, was measured the eficiency over a circulating thermal fluid. The stagnation temperature measured in december was 476,5°C, at 4:25PM. The second part of tests has shown an efficiency of 33% on first one assay. However when was utilizing another form to measure the solar irradiation (theoretic approach), the efficiency rises between 45% to 55%, regarding steady state conditions. Furthermore, this work allowed discussions to discover ways to increase the energy efficiency.